Efficacy of left subclavian artery laser in situ fenestration combined with hybrid arch debranching surgery for aortic arch reconstruction in patients with Stanford type A aortic dissection - Zhang, Qi; Zhao, Hao; Yue, Yongqiang; Zhang, Shuai; Sun, Likun; Xu, Peng; Liu, Chao; Hua, Zhaohui; Li, Zhen (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveTo investigate the early and mid-term outcomes of in situ laser fenestration (ISLF) of the left subclavian artery (LSA) combined with hybrid aortic arch debranching for aortic arch reconstruction in Stanford type A aortic dissection.MethodsThis retrospective study analyzed 57 patients (60+ years) treated from 2018 to 2023. LSA reconstruction-related complications were defined as: anastomotic bleeding, LSA occlusion, stent migration, or fenestration-related endoleak. Patients were divided into ISLF + debranching (n = 29) and debranching-only (n = 28) groups. Outcomes were compared using t-tests and Kaplan–Meier analysis.ResultsThe ISLF group had shorter operative time (323.1 ± 10.3 vs. 329.4 ± 7.2 min, P = 0.009) and higher LSA reconstruction success (100% vs. 75%, P = 0.013). LSA complication rates were lower in the ISLF group (3.4% vs. 28.6%, P = 0.025). Five-year survival was similar (79.3% vs. 75.0%, P = 0.575).ConclusionISLF with hybrid debranching improves LSA reconstruction success and reduces complications without affecting survival.